Interstícios: colaboração para os estudos semióticos dos textos com memória própria - Freire, Norma Leonor Hall (2013)
A text has the ability to preserve the memory of their prior contexts. Without this function there would be no Story. If a text remained in the observer's consciousness only as itself, the past would be as a mosaic of disconnected fragments. Did mine, in the approach of the Conto de Amaro, the words of Yury Lotman. The objective of the present research in relation to Conto de Amaro, a 15thcentury narrative produced in the monastery of Alcobaça in Portugal, regarded as an enigma in the context of medieval literature is, before unveiling the origins, give a voice to the narrative. For that other texts were needed. The internal element of the tale of Amaro that allows better visibility of similar situations is the distinct temporalities living in the same narrative space. The application of the comparative method to this larger constellation with the 14 texts of research support, produced an extensive network of meanings embedded in some way to the Conto de Amaro that you can call its own memory. The identification of these meanings in the communicative mediation of culture mapped by Jesús Martín-Barbero - socialibility, institutionality, technicality, and rituality- allowed an interpretation of the tale of Amaro on several levels that are its own by adding understanding the text. At the same time, generated the perception of two distinct logics operating inside and outside the text, which called for understanding. One of them, different from that which is characteristic of descriptive and explanatory thought that, somehow, can be called the language of names. The functioning of names is so different on the set of natural languages, they can be considered a separate language. Their presence, however, is sensitive in the substrate of the cultures and the heterogeneity of human consciousness. The space they inhabit is mosaicado, their temporality is distinct and their nature is symbols. In the research, I indicate its presence and made a few comments. Among the authors who helped immensely in understanding the goal I quote Jerusa Pires Ferreira, Aron Gurevitch, Claude Lévi-Strauss, Yuri Lotman, Roman Jakobson, Boris Uspenski, Vyacheslav Ivanov and Santo Amaro